Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd002137.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Reduced or modified dietary fat for preventing cardiovascular disease

Abstract: Background Reduction and modification of dietary fats have differing effects on cardiovascular risk factors (such as serum cholesterol), but their effects on important health outcomes are less clear. Objectives To assess the effect of reduction and/or modification of dietary fats on mortality, cardiovascular mortality, cardiovascular morbidity and individual outcomes including myocardial infarction, stroke and cancer diagnoses in randomised clinical trials of at least 6 months duration. Search methods For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 538 publications
3
42
1
3
Order By: Relevance
“…The other two significant findings were related to cardiovascular disease (CVD) events and not mortality 50 55. In 2011, including RCTs with a minimum of 6 months duration, Hooper et al found 1 significant result and 11 non-significant results.…”
Section: Resultsmentioning
confidence: 99%
“…The other two significant findings were related to cardiovascular disease (CVD) events and not mortality 50 55. In 2011, including RCTs with a minimum of 6 months duration, Hooper et al found 1 significant result and 11 non-significant results.…”
Section: Resultsmentioning
confidence: 99%
“…levels <10 en% and preferably lower [1,18], are recommended to reduce the long-term risk of heart disease [18]. Even at a young age, high dietary intakes of SFA have been shown to increase plasma total and LDL cholesterol concentrations and could enhance vascular lipid deposition and the occurrence of early vascular lesions [57,58,59,60]. In the Special Turku Coronary Risk Factor Intervention Project (STRIP), 1,000 healthy infants were randomized to a low-saturated-fat, low-cholesterol diet counseling group and a control group and were followed every 6-12 months throughout childhood.…”
Section: Resultsmentioning
confidence: 99%
“…Cerebrovascular disease (CVD) is the third most common cause of death worldwide [1,2]. CVD accounts for the major cause of morbidity and mortality in industrialized countries and responsible for stroke and transient ischemic attack (TIA) [3,4].…”
Section: Introductionmentioning
confidence: 99%